STUDY OF STRUCTURAL-MECHANICAL PROPERTIES OF VINPOCETINE SUPPOSITORIES - N. А. Nagornaya; B. S. Burlaka; S. А. Gladyshevа (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Using alternative absorption path for vinpocetine, in particular rectal, will allow to improve its bioavailability, efficiency in comparison with traditional oral dosage forms and will provide practical cardiology with accessible domestic pharmaco-therapeutic product.